Julia Sabina GUTIÉRREZ.— Rafael Azcona: el guionista como creador. Madrid: Pigmalión, 2018, 408 pp. (David Felipe Arranz) - ARRANZ, David Felipe (Signa: Revista de la Asociación Española de Semiótica, 2022)